Efektivitas Edukasi Pengetahuan Tentang Bahaya Merokok Melalui Video Pembelajaran Pada Anak Remaja - Jhonny Angky; Saleh, Muh; Baharuddin; Amaliah Syam, Aziqhah (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
Smoking is a major health problem that has a significant impact on general health as well as oral and dental health. Adolescents are considered a vulnerable group because they are easily influenced by social environments and have limited knowledge. This study aimed to evaluate the effectiveness of education through learning videos in improving adolescents’ knowledge about the dangers of smoking. The study employed a pre-experimental design with a one-group pretest– posttest approach, involving 77 seventh- and eighth-grade students of SMP Nasional Makassar selected using purposive sampling. The instrument used was a questionnaire consisting of 15 multiple-choice questions. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of α = 0.05. The findings indicated an increase in the mean knowledge score from 9.26 (SD = 3.412) in the pretest to 12.29 (SD = 1.932) in the posttest. The proportion of respondents with good knowledge increased from 50.6% to 72.7%, while those in the poor category decreased from 19.5% to 0%. The Wilcoxon test result showed p < 0.001, indicating a significant difference between conditions before and after the intervention. This study concludes that the use of learning videos can effectively enhance adolescents’ knowledge regarding the dangers of smoking, particularly related to oral and dental health. Audiovisual media can serve as an engaging and easily understood alternative method for health promotion among adolescents.